Acumulación De Restos Lignino-Celulósicos (Necromasa) En Un Bosque Templado De Antiguo Crecimiento Dominado Por Nothofagus En El Centro- Sur De Chile - Pinargote, Carlos Belezaca; Piloso, Darwin Salvatierra; Campusano, Diana Delgado; Bórquez, Roberto Godoy; Flores, Eduardo Valenzuela; Romero, Edwin Jiménez; Tobar, Rolando López; Mite, Renato Baque; Anangono, Roberto Herrera; Bayas, Byron Oviedo; Arevalo, María Cadme; Barros, Tito Bohórquez; et al. (European Scientific Journal, ESJ, 2016)
Coarse woody debris (CWD) are the necromass in wooded environments and comply with various ecosystems functions, such as seedling nursery, habitat other organisms, store carbon (C) and nutrients, etc.. Volume, necromass, and decay states of CWD dead in an old-growth temperate (OGTF) forest in Puyehue National Park, South-Central Chile were evaluated. In 10 plots of 900 m2 CWD was quantified (≥ 10 cm diameter), whose necromass classified using a scale of five categories/stages of decay, necromass (1 = lowest and 5 = highest degradation). The average forest density was 299 trees ha-1, 112 m2 ha-1 of basal area, and 2.395 m3 of stem volume. The upper arboreal stratum was dominated by N. betuloides. The greatest amount of CWD belonged to N. betuloides (95,2%), where logs (52,7%) and branches (35%), plant structures were present in greater numbers. The bulk of necromass found in advanced states of decomposition (level 4 and 5) with 56,5% and 34,1%, respectively. It was determined that the CWD volume was 632 m3 ha-1, representing a necromass of 321.5 Mg ha- 1. These results demonstrate that the old-growth temperate forests of southern Chile are significant reserves of coarse woody debris, which contributes to the biogeochemistry of these complex and remote ecosystems.